Pan-continental assessment of socioeconomic and environmental predictors of PFAS occurrence in European rivers from a harmonised monitoring study - Jun Li; Alistair B.A. Boxall; Caroline Swan; Selwyn Hoeks; Racliffe W.S. Lai; John L. Wilkinson; Recep C. Altinbag; Åsa Arrhenius; Roman Ashauer; Thomas Backhaus; Besnik Baraj; Vasiliki G. Beretsou; et al. (Water Research, 2026)

What happened with the smaller ones? First comprehensive taphonomic analysis of microvertebrates from the Late Pleistocene of Rancho La Brea (Los Angeles, USA) - Fernando J. Fernández; Claudia I. Montalvo; M. Dolores Marin‐Monfort; Renata Sostillo; Daiana G. Coll; Emily Lindsey; Karin A. Rice; Gary T. Takeuchi; Rodrigo L. Tomassini (Journal of Quaternary Science, 2025)
Rancho La Brea (RLB) in Los Angeles, USA, is an iconic fossil locality, owing to the high number and diversity of Quaternary vertebrate remains and their excellent preservation. More than a century of study, focused predominantly on large mammals, has provided valuable information along different lines of research, including taxonomy, taphonomy, isotopic ecology, functional morphology, and paleopathology. In order to develop a better understanding of the formation of this site, we conducted a taphonomic study of the microvertebrates, using samples from asphalt seeps dating to before the Last Glacial Maximum. The taphonomic evidence suggests that direct entrapment is the most plausible process to explain the primary accumulation of the thousands of microvertebrate remains. Based on the absence of digestive corrosion and feeding marks, low percentages of juvenile individuals, relative abundance patterns, and anatomical indices (postcranial elements vs. cranial elements and distal vs. proximal limb elements), the activity of predators/scavengers is ruled out as a primary process in producing the assemblages, although other processes, such as water transport of skeletal elements from nearby areas, could also have played a role in the formation of the deposits. The occurrence of successive entrapments and episodes of fluvial transportation, combined with post‐depositional internal movement within the seeps, would have given rise to the development of time‐averaged assemblages produced through a complex interplay of factors.

New Fishing Strategies to Face Climate Change Effects on the Spanish Tropical Tuna Fisheries Off Indian Ocean - José Carlos Báez; Ivone A. Czerwinski; María Lourdes Ramos; José María Bellido; Marta Coll (Fisheries Oceanography, 2025)
Tropical tunas, including yellowfin ( Thunnus albacares ), are recognized as a crucial contributor to global food security. Moreover, yellowfin tuna is the most commercially valuable tropical tuna. The Spanish purse seine freezer fleet, actively operating in the Indian Ocean, emerges as a leading contributor to the global yellowfin tuna catch. Currently, the planet is undergoing a climate change, which is poised to alter habitats on a global scale, particularly impacting tropical regions by causing an increase in sea surface temperatures at an unprecedented rate as well as ocean deoxygenation. Consequently, it is foreseeable that large pelagic highly migratory species like tunas may shift their distribution areas, resulting in the translocation of the current fishing grounds. In this context, the main goal of this work is to study the potential shifts of the Spanish purse seine fishing grounds targeting yellowfin tuna within the tropical belt in the Indian Ocean. Our findings suggest that although the largest yellowfin tuna catches have moved northward in latitude, most of the fishing effort, indicated by the greater number of fishing sets, has been located toward the equatorial region. Present results can only be interpreted from a human perspective and following a commercial strategy in response to the management of yellowfin tuna. Therefore, according to the 38 years of the analyzed dataset, a shift in fleet dynamics is apparent. However, we suggest that this new fishing strategy could be not so much attributed to the movement of free schools toward higher latitudes but to complex trade‐off strategies.

From the lab to the river: Bimetallic clinoptilolite photocatalyst for antibiotic-resistant bacteria and emerging contaminants removal - Paula Prieto-Laria; Antonia Jiménez-Rodríguez; A. Rabdel Ruiz-Salvador; Inés Canosa; Amando Flores; Yamilet Coll; Katia Borrego; Nuria O. Nuñez; Esteban Alonso; Pilar Fernández-Ibáñez; Tania Farias; Menta Ballesteros (Journal of Environmental Chemical Engineering, 2025)

Spatiotemporal patterns of public attention to invasive species across an invasion front: a case study of lionfish (Pterois miles) from the Mediterranean Sea - Lara Fazzari; Reut Vardi; Ivan Jaric; Ricardo A. Correia; Marta Coll; Valerio Sbragaglia (Biological Invasions, 2024)
Understanding societal interest in invasive species is crucial as greater public attention can support the success of conservation efforts. One of the main challenges in monitoring societal interest to support conservation is the absence of near-real-time indicators to track large-scale spatiotemporal dynamics of public attention. However, the digital revolution has opened up new opportunities to develop such indicators in support of invasive species research and management. Here, we aim to evaluate public awareness and interest in the invasive lionfish ( Pterois miles ) in the Mediterranean Sea and investigate spatiotemporal patterns of public interest in the species along its invasion front by using Google search volumes as a proxy for public attention. We implemented topic searches for the lionfish to download Google search volumes from 2013 to 2022 and used these data to test two hypotheses: (1) countries experiencing lionfish invasion exhibit higher public attention than those without lionfish, and (2) in invaded countries, public attention peaks around the arrival year, followed by a decline to baseline levels. Our study confirmed the first hypothesis, showing higher public attention in invaded countries. However, temporal patterns of attention did not fully align with the year of lionfish arrival, suggesting that the socio-political complexity of the region (e.g., cultural trends or internet accessibility), may be a key aspect to consider in future studies. Overall our study shows that digital data sources provide a unique opportunity to monitor social aspects of biological invasions with low associated costs and quick access to a great amount of data generated by internet users.

Top predator status and trends: ecological implications, monitoring and mitigation strategies to promote ecosystem-based management - Caterina Maria Fortuna; Tomaso Fortibuoni; Juan Bueno-Pardo; Marta Coll; Anita Franco; Joan Giménez; Yolanda Stranga; Myron A. Peck; Cristina Claver; Sophie Brasseur; Elena Fernández-Corredor; Simonetta Fraschetti; et al. (Frontiers in Marine Science, 2024)
The conservation and management of marine ecosystems hinge on a comprehensive understanding of the status and trends of top predators. This review delves into the ecological significance of marine top predators, examining their roles in maintaining ecosystem stability and functioning through an integrated analysis of current scientific literature. We first assess the efficacy of various monitoring methods, ranging from traditional field observations to cutting-edge technologies like satellite tracking and environmental DNA (eDNA) analysis and evaluating their strengths and limitations in terms of accuracy, spatial coverage, and cost-effectiveness, providing resource managers with essential insights for informed decision-making. Then, by synthesizing data from diverse marine ecosystems, this study offers a comprehensive overview of the trends affecting top predator populations worldwide. We explore the multifaceted impacts of human activities, climate change, and habitat degradation on the abundance and distribution of these key species. In doing so, we shed light on the broader implications of declining top predator populations, such as trophic cascades and altered community structures. Following a thorough assessment of successful strategies for reversing the decline of top predators, a compilation of recommendations is presented, encompassing effective governance interventions. A crucial aspect of effective ecosystem-based management is the implementation of robust monitoring strategies. Mitigation measures are imperative to reverse the adverse impacts on marine top predators. We present a comprehensive array of mitigation options based on successful case studies. These include the establishment of marine protected areas, the enforcement of fisheries regulations, and the promotion of sustainable fishing practices. We deepen the synergies between these strategies and their potential to mitigate human-induced stressors on top predator populations to safeguard their pivotal role in maintaining marine ecosystem structure and function. By examining marine top predators’ ecological significance, analyzing population trends, discussing monitoring techniques, and outlining effective mitigation strategies, we provide a comprehensive resource for researchers, policymakers, and stakeholders engaged in fostering ecosystem-based management approaches. We conclude that integrating these insights into current management frameworks will be essential to safeguard both top predators and the broader marine environment for future generations.

Current Trends and Future Directions in Urban Social Prescribing - J. S. Litt; L. Coll-Planas; A. L. Sachs; M. Masó Aguado; M. Howarth (Current Environmental Health Reports, 2023)

Making protected areas effective for biodiversity, climate and food - Almut Arneth; Paul Leadley; Joachim Claudet; Marta Coll; Carlo Rondinini; Mark D. A. Rounsevell; Yunne‐Jai Shin; Peter Alexander; Richard Fuchs (Global Change Biology, 2023)
The spatial extent of marine and terrestrial protected areas (PAs) was among the most intensely debated issues prior to the decision about the post‐2020 Global Biodiversity Framework (GBF) of the Convention on Biological Diversity. Positive impacts of PAs on habitats, species diversity and abundance are well documented. Yet, biodiversity loss continues unabated despite efforts to protect 17% of land and 10% of the oceans by 2020. This casts doubt on whether extending PAs to 30%, the agreed target in the Kunming‐Montreal GBF, will indeed achieve meaningful biodiversity benefits. Critically, the focus on area coverage obscures the importance of PA effectiveness and overlooks concerns about the impact of PAs on other sustainability objectives. We propose a simple means of assessing and visualising the complex relationships between PA area coverage and effectiveness and their effects on biodiversity conservation, nature‐based climate mitigation and food production. Our analysis illustrates how achieving a 30% PA global target could be beneficial for biodiversity and climate. It also highlights important caveats: (i) achieving lofty area coverage objectives alone will be of little benefit without concomitant improvements in effectiveness, (ii) trade‐offs with food production particularly for high levels of coverage and effectiveness are likely and (iii) important differences in terrestrial and marine systems need to be recognized when setting and implementing PA targets. The CBD's call for a significant increase in PA will need to be accompanied by clear PA effectiveness goals to reduce and revert dangerous anthropogenic impacts on socio‐ecological systems and biodiversity.

Bottom-up effect of nitrogen fertilization on the density of the corn leafhopper and its impact on both disease incidence and natural parasitism - Eduardo G. Virla; Erica B. Luft Albarracín; Cecilia Díaz; Guido A. Van Nieuwenhove; Franco D. Fernández; María V. Coll Aráoz; Nicolás A. Melchert; Luis R. Conci; María P. Giménez Pecci (Journal of Pest Science, 2023)

Special issue on recent advances in zoophytophagous arthropods for agroecosystems sustainability - Alberto Urbaneja; Moshe Coll; Josep A. Jaques; Jose Eduardo Serrao; Dionysios Perdikis; Amy L. Roda (Journal of Pest Science, 2022)

Recreational angling and spearfishing on social media: insights on harvesting patterns, social engagement and sentiments related to the distributional range shift of a marine invasive species - Valerio Sbragaglia; Lucía Espasandín; Salvatore Coco; Alberto Felici; Ricardo A. Correia; Marta Coll; Robert Arlinghaus (Reviews in Fish Biology and Fisheries, 2022)

Performance and host finding behavior in relation to host age of Cosmocomoidea annulicornis, egg parasitoid of a sharpshooter vector of the citrus variegated chlorosis - Carolina Manzano; Nicolás A. Melchert; Maria V. Coll Araoz; Eduardo G. Virla; Erica Luft Albarracin (BioControl, 2022)

Born With Bristles: New Insights on the Kölliker’s Organs of Octopus Skin - Roger Villanueva; Montserrat Coll-Lladó; Laure Bonnaud-Ponticelli; Sergio A. Carrasco; Oscar Escolar; Fernando Á. Fernández-Álvarez; Ian G. Gleadall; Jaruwat Nabhitabhata; Nicolás Ortiz; Carlos Rosas; Pilar Sánchez; Janet R. Voight; et al. (Frontiers in Marine Science, 2021)
The entire skin surface of octopus embryos, hatchlings and juveniles bears scattered tufts of tiny chitinous setae within small pockets, from which they can be everted and retracted. Known as Kölliker’s organs (KO), they disappear before the subadult stage. The function of these structures during the early life of the octopus is unknown, despite having been first described nearly two centuries ago. To investigate these organs further, general trends in size of KO distribution and density were analyzed in hatchlings and juveniles of 17 octopod species from all oceans, representing holobenthic, holopelagic and meropelagic modes of life. The size of the KO is fairly constant across species, unrelated to mode of life or hatchling size. The density of KO is similar on ventral and dorsal body surfaces, but hatchlings of smaller size tend to have a higher density of KO on the aboral surface of the arms. Analysis of a series of post-hatching Octopus vulgaris shows KO size to be constant throughout ontogeny; it is therefore a consistent structure during the octopus early life from planktonic hatchling to benthic juvenile. New KO are generated on the skin of the arm tips during the planktonic period and initial benthic lives of juveniles. Their density, on both the mantle and arms, gradually decreases as the octopus grows. In older benthic juveniles, the KO degrades, losing its setae and the base of its follicle becomes exposed as a nearly circular stump of muscle. It is estimated that fully everted KO increase the body surface area by around two-thirds compared to when the KO are retracted. This modular mechanism of body surface extension and roughness probably influences flow-related forces such as drag and propulsion of the moving surface of the young octopus while it is of small size with a relatively large surface area. In addition, the distribution of these organs on the aboral surface of the arms of the octopus and their birefringent properties suggest a role in camouflage. Further research is needed to test these hypotheses of KO function in live animals.

Advancing Global Ecological Modeling Capabilities to Simulate Future Trajectories of Change in Marine Ecosystems - Marta Coll; Jeroen Steenbeek; Maria Grazia Pennino; Joe Buszowski; Kristin Kaschner; Heike K. Lotze; Yannick Rousseau; Derek P. Tittensor; Carl Walters; Reg A. Watson; Villy Christensen (Frontiers in Marine Science, 2020)

The Ocean Decade: A True Ecosystem Modeling Challenge - Johanna J. Heymans; Alida Bundy; Villy Christensen; Marta Coll; Kim de Mutsert; Elizabeth A. Fulton; Chiara Piroddi; Yunne-Jai Shin; Jeroen Steenbeek; Morgane Travers-Trolet (Frontiers in Marine Science, 2020)

Contrasting patterns of tree species mixture effects on wood δ13C along an environmental gradient - G. de Streel; C. Collet; I. Barbeito; K. Bielak; A. Bravo-Oviedo; G. Brazaitis; L. Coll; L. Drössler; D. Forrester; M. Heym; M. Löf; M. Pach; et al. (European Journal of Forest Research, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Photo‐identification as a tool to study small‐spotted catshark Scyliorhinus canicula - J. Navarro; A. Perezgrueso; C. Barría; M. Coll (Journal of Fish Biology, 2018)
Photo‐identification (photo‐ID) was tested as a means to identify individual small‐spotted catsharks Scyliorhinus canicula . The spotting pattern of the caudal region of S. canicula was used for the tests and revealed that photo‐ID is an efficient method to identify individuals. Photo‐ID is logistically simple, making it a potential alternative to traditional tagging to provide information on the distribution patterns and population dynamics of S. canicula and related species.

Strong fisheries management and governance positively impact ecosystem status - Alida Bundy; Ratana Chuenpagdee; Jennifer L Boldt; Maria de Fatima Borges; Mohamed Lamine Camara; Marta Coll; Ibrahima Diallo; Clive Fox; Elizabeth A Fulton; Ayse Gazihan; Astrid Jarre; Didier Jouffre; et al. (Fish and Fisheries, 2017)
Fisheries have had major negative impacts on marine ecosystems, and effective fisheries management and governance are needed to achieve sustainable fisheries, biodiversity conservation goals and thus good ecosystem status. To date, the IndiSeas programme (Indicators for the Seas) has focussed on assessing the ecological impacts of fishing at the ecosystem scale using ecological indicators. Here, we explore fisheries ‘Management Effectiveness’ and ‘Governance Quality’ and relate this to ecosystem health and status. We developed a dedicated expert survey, focused at the ecosystem level, with a series of questions addressing aspects of management and governance, from an ecosystem‐based perspective, using objective and evidence‐based criteria. The survey was completed by ecosystem experts (managers and scientists) and results analysed using ranking and multivariate methods. Results were further examined for selected ecosystems, using expert knowledge, to explore the overall findings in greater depth. Higher scores for ‘Management Effectiveness’ and ‘Governance Quality’ were significantly and positively related to ecosystems with better ecological status. Key factors that point to success in delivering fisheries and conservation objectives were as follows: the use of reference points for management, frequent review of stock assessments, whether Illegal, Unreported and Unregulated ( IUU ) catches were being accounted for and addressed, and the inclusion of stakeholders. Additionally, we found that the implementation of a long‐term management plan, including economic and social dimensions of fisheries in exploited ecosystems, was a key factor in successful, sustainable fisheries management. Our results support the thesis that good ecosystem‐based management and governance, sustainable fisheries and healthy ecosystems go together.

Flower structure and developmental stages of the capitulum of Smallanthus sonchifolius (Asteraceae): reproductive implications - M. S. Ibañez; M. I. Mercado; M. V. Coll Aráoz; M. L. Zannier; A. Grau; G. I. Ponessa (Journal of Plant Research, 2017)

Ecosystem effects of invertebrate fisheries - Tyler D Eddy; Heike K Lotze; Elizabeth A Fulton; Marta Coll; Cameron H Ainsworth; Júlio Neves de Araújo; Catherine M Bulman; Alida Bundy; Villy Christensen; John C Field; Neil A Gribble; Mejs Hasan; et al. (Fish and Fisheries, 2017)
Since the 1950s, invertebrate fisheries catches have rapidly expanded globally to more than 10 million tonnes annually, with twice as many target species, and are now significant contributors to global seafood provision, export, trade and local livelihoods. Invertebrates play important and diverse functional roles in marine ecosystems, yet the ecosystem effects of their exploitation are poorly understood. Using 12 ecosystem models distributed worldwide, we analysed the trade‐offs of various invertebrate fisheries and their ecosystem effects as well as ecological indicators. Although less recognized for their contributions to marine food webs, our results show that the magnitude of trophic impacts of invertebrates on other species of commercial and conservation interest is comparable with those of forage fish. Generally, cephalopods showed the strongest ecosystem effects and were characterized by a strong top‐down predatory role. Lobster, and to a lesser extent, crabs, shrimp and prawns, also showed strong ecosystem effects, but at lower trophic levels. Benthic invertebrates, including epifauna and infauna, also showed considerable ecosystem effects, but with strong bottom‐up characteristics. In contrast, urchins, bivalves, and gastropods showed generally lower ecosystem effects in our simulations. Invertebrates also strongly contributed to benthic–pelagic coupling, with exploitation of benthic invertebrates impacting pelagic fishes and vice versa. Finally, on average, invertebrates produced maximum sustainable yield at lower levels of depletion (~45%) than forage fish (~65%), highlighting the need for management targets that avoid negative consequences for target species and marine ecosystems as a whole.

The amino-terminal domain of ORF149 of koi herpesvirus is preferentially targeted by IgM from carp populations surviving infection - F. Torrent; A. Villena; P. A. Lee; W. Fuchs; S. M. Bergmann; J. M. Coll (Archives of Virology, 2016)

Both Volatiles and Cuticular Plant Compounds Determine Oviposition of the Willow Sawfly Nematus oligospilus on Leaves of Salix spp. (Salicaceae) - Celina L. Braccini; Andrea S. Vega; M. Victoria Coll Aráoz; Peter E. Teal; Teresa Cerrillo; Jorge A. Zavala; Patricia C. Fernandez (Journal of Chemical Ecology, 2015)

Growth and yield of mixed versus pure stands of Scots pine (Pinus sylvestris L.) and European beech (Fagus sylvatica L.) analysed along a productivity gradient through Europe - H. Pretzsch; M. del Río; Ch. Ammer; A. Avdagic; I. Barbeito; K. Bielak; G. Brazaitis; L. Coll; G. Dirnberger; L. Drössler; M. Fabrika; D. I. Forrester; et al. (European Journal of Forest Research, 2015)

Modelling dynamic ecosystems: venturing beyond boundaries with the Ecopath approach - M. Coll; E. Akoglu; F. Arreguín-Sánchez; E. A. Fulton; D. Gascuel; J. J. Heymans; S. Libralato; S. Mackinson; I. Palomera; C. Piroddi; L. J. Shannon; J. Steenbeek; et al. (Reviews in Fish Biology and Fisheries, 2015)

The global ocean is an ecosystem: simulating marine life and fisheries - Villy Christensen; Marta Coll; Joe Buszowski; William W. L. Cheung; Thomas Frölicher; Jeroen Steenbeek; Charles A. Stock; Reg A. Watson; Carl J. Walters (Global Ecology and Biogeography, 2015)
Aim There has been considerable effort allocated to understanding the impact of climate change on our physical environment, but comparatively little to how life on Earth and ecosystem services will be affected. Therefore, we have developed a spatial–temporal food web model of the global ocean, spanning from primary producers through to top predators and fisheries. Through this, we aim to evaluate how alternative management actions may impact the supply of seafood for future generations. Location Global ocean. Methods We developed a modelling complex to initially predict the combined impact of environmental parameters and fisheries on global seafood production, and initially evaluated the model's performance through hindcasting. The modelling complex has a food web model as core, obtains environmental productivity from a biogeochemical model and assigns global fishing effort spatially. We tuned model parameters based on M arkov chain random walk stock reduction analysis, fitting the model to historic catches. We evaluated the goodness‐of‐fit of the model to data for major functional groups, by spatial management units and globally. Results This model is the most detailed ever constructed of global fisheries, and it was able to replicate broad patterns of historic fisheries catches with best agreement for the total catches and good agreement for species groups, with more variation at the regional level. Main conclusions We have developed a modelling complex that can be used for evaluating the combined impact of fisheries and climate change on upper‐trophic level organisms in the global ocean, including invertebrates, fish and other large vertebrates. The model provides an important step that will allow global‐scale evaluation of how alternative fisheries management measures can be used for mitigation of climate change.

BAAD: a Biomass And Allometry Database for woody plants - Daniel S. Falster; Remko A. Duursma; Masae I. Ishihara; Diego R. Barneche; Richard G. FitzJohn; Angelica Vårhammar; Masahiro Aiba; Makoto Ando; Niels Anten; Michael J. Aspinwall; Jennifer L. Baltzer; Christopher Baraloto; et al. (Ecology, 2015)
Understanding how plants are constructed—i.e., how key size dimensions and the amount of mass invested in different tissues varies among individuals—is essential for modeling plant growth, carbon stocks, and energy fluxes in the terrestrial biosphere. Allocation patterns can differ through ontogeny, but also among coexisting species and among species adapted to different environments. While a variety of models dealing with biomass allocation exist, we lack a synthetic understanding of the underlying processes. This is partly due to the lack of suitable data sets for validating and parameterizing models. To that end, we present the Biomass And Allometry Database (BAAD) for woody plants. The BAAD contains 259 634 measurements collected in 176 different studies, from 21 084 individuals across 678 species. Most of these data come from existing publications. However, raw data were rarely made public at the time of publication. Thus, the BAAD contains data from different studies, transformed into standard units and variable names. The transformations were achieved using a common workflow for all raw data files. Other features that distinguish the BAAD are: (i) measurements were for individual plants rather than stand averages; (ii) individuals spanning a range of sizes were measured; (iii) plants from 0.01–100 m in height were included; and (iv) biomass was estimated directly, i.e., not indirectly via allometric equations (except in very large trees where biomass was estimated from detailed sub‐sampling). We included both wild and artificially grown plants. The data set contains the following size metrics: total leaf area; area of stem cross‐section including sapwood, heartwood, and bark; height of plant and crown base, crown area, and surface area; and the dry mass of leaf, stem, branches, sapwood, heartwood, bark, coarse roots, and fine root tissues. We also report other properties of individuals (age, leaf size, leaf mass per area, wood density, nitrogen content of leaves and wood), as well as information about the growing environment (location, light, experimental treatment, vegetation type) where available. It is our hope that making these data available will improve our ability to understand plant growth, ecosystem dynamics, and carbon cycling in the world's vegetation.

Long-term outcomes of risk-reducing surgery in unaffected women at increased familial risk of breast and/or ovarian cancer - Louise Heiniger; Phyllis N. Butow; Joseph Coll; Tracey Bullen; Judy Wilson; Brandi Baylock; Bettina Meiser; Melanie A. Price (Familial Cancer, 2015)

Risk of intrauterine growth restriction among HIV-infected pregnant women: a cohort study - M. López; M. Palacio; A. Goncé; S. Hernàndez; F. J. Barranco; L. García; M. Loncà; J. O. Coll; E. Gratacós; F. Figueras (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

Variability in sesquiterpene lactones from the leaves of yacon (Smallanthus sonchifolius) accessions of different geographic origin - María Inés Mercado; María Victoria Coll Aráoz; Iván Manrique; Alfredo Grau; César A. N. Catalán (Genetic Resources and Crop Evolution, 2014)

Semiochemical and natural product-based approaches to control Spodoptera spp. (Lepidoptera: Noctuidae) - A. Guerrero; Edi A. Malo; J. Coll; C. Quero (Journal of Pest Science, 2014)

Ontogeny and total sugar content of yacon tuberous roots and other three Smallanthus species (Heliantheae, Asteraceae), insights on the development of a semi-domesticated crop - María V. Coll Aráoz; Alejandra M. Kortsarz González; María I. Mercado; Graciela I. Ponessa; Alfredo Grau; César A. N. Catalán (Genetic Resources and Crop Evolution, 2014)

Exploring Patterns of Seafood Provision Revealed in the Global Ocean Health Index - Kristin M. Kleisner; Catherine Longo; Marta Coll; Ben S. Halpern; Darren Hardy; Steven K. Katona; Frédéric Le Manach; Daniel Pauly; Andrew A. Rosenberg; Jameal F. Samhouri; Courtney Scarborough; U. Rashid Sumaila; et al. (Ambio, 2013)

Matrix metalloproteinase expression and activity in trophoblast-decidual tissues at organogenesis in CF-1 mouse - Vanina Fontana; Tamara A. Coll; Cristian M. A. Sobarzo; Leticia Perez Tito; Juan Carlos Calvo; Elisa Cebral (Journal of Molecular Histology, 2012)

Serotype 3 is a common serotype causing invasive pneumococcal disease in children less than 5 years old, as identified by real-time PCR - L. Selva; P. Ciruela; C. Esteva; M. F. Sevilla; G. Codina; S. Hernandez; F. Moraga; J. J. García-García; A. Planes; F. Coll; I. Jordan; N. Cardeñosa; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Historical Changes in Marine Resources, Food-web Structure and Ecosystem Functioning in the Adriatic Sea, Mediterranean - Heike K. Lotze; Marta Coll; Jennifer A. Dunne (Ecosystems, 2011)

Hyperspectral indices for detecting changes in canopy reflectance as a result of underground natural gas leakage - M. F. Noomen; K. L. Smith; J. J. Colls; M. D. Steven; A. K. Skidmore; F. D. Van Der Meer (International Journal of Remote Sensing, 2008)

Anthraquinones from in vitro root culture of Morinda royoc L. - Janetsy Borroto; Josep Coll; Maribel Rivas; Maria Blanco; Oscar Concepción; Yudelsy A. Tandrón; Martha Hernández; Reinaldo Trujillo (Plant Cell, Tissue and Organ Culture (PCTOC), 2008)

neo-Clerodane diterpenoids from Ajuga: structural elucidation and biological activity - Josep Coll; Yudelsy A. Tandrón (Phytochemistry Reviews, 2007)

Geographic variations in seed dispersal by ants: are plant and seed traits decisive? - R. Boulay; J. Coll-Toledano; A. J. Manzaneda; X. Cerdá (The Science of Nature, 2007)

The Systemic Absorption of Etoposide after Intravaginal Administration in Patients with Cervical Intraepithelial Lesions Associated with Human Papillomavirus Infection - P. García-López; M. Coll; E. Cervera; L. Reyes-Vermot; M. A. Torres; G. Ábrego-Pérez; A. I. Hernández-Pájaro; G. Castañeda-Hernandez; A. Mohar-Betancourt; A. Meneses (Pharmaceutical Research, 2006)

Medical speciality and pattern of medicines prescription - A. Vallano; E. Montan; J. M. Arnau; X. Vidal; C. Pallars; M. Coll; J. R. Laporte (European Journal of Clinical Pharmacology, 2004)

Improvement of Transfection Efficiency of Epithelioma Papulosum Cyprini Carp Cells by Modification of Cell Cycle and Use of an Optimal Promoter - A. Rocha; S. Ruiz; J. M. Coll (Marine Biotechnology, 2004)

Application of Inducible and Targeted Gene Strategies to Produce Transgenic Fish: A Review - A. Rocha; S. Ruiz; A. Estepa; J. M. Coll (Marine Biotechnology, 2004)

Detection of QTL affecting fatty acid composition in the pig - Alex Clop; Cristina Ovilo; Miguel Perez-Enciso; Albert Cercos; Anna Tomas; Ana Fernandez; Agustina Coll; Josep M. Folch; Carmen Barragan; Isabel Diaz; Maria A. Oliver; Luis Varona; et al. (Mammalian Genome, 2003)

Improvement of DNA transfection with cationic liposomes - A. Rocha; S. Ruiz; J. M. Coll (Journal of Physiology and Biochemistry, 2002)

Transfection of epithelioma papulosum cyprini (EPC) carp cells - A. Lopez; M. Fernandez-Alonso; A. Rocha; A. Estepa; J.M. Coll (Biotechnology Letters, 2001)

Abstracts of Presentations at the 18th Conference of the Entomological Society of Israel - M. P. Pener; L. Anshelevich; E. Dunkelblum; M. Hard; A. Harari; D. Gordon; M. Kehat; H. Reuveny; O. Akunis; D. Oppenheim; E. Dunkelblum; Acta Rafaeli; et al. (Phytoparasitica, 2001)

Abstracts of papers presented at the 16th conference of the Entomological Society of Israel Research on thrips in Israel Dedicated to the Memory of Prof. E. Rivnay on the 100th Anniversary of his Birth - M. Wysoki; M. Wysoki; M. Klein; M. Davidovich; R. Shaked; K. Rosenfeld; E. Pressman; Phyllis G. Weintraub; A. R. Horowitz; Sophia Kleitman; R. Azari; Leah Tsror; et al. (Phytoparasitica, 1999)

Activation and desensitization by cyclic antidepressant drugs of α2-autoreceptors, α2-heteroreceptors and 5-HT1A-autoreceptors regulating monoamine synthesis in the rat brain in vivo - S. Esteban; J. Lladó; A. Sastre-Coll; J.A. García-Sevilla (Naunyn-Schmiedeberg's Archives of Pharmacology, 1999)

Effects of imidazoline receptor ligands on monoamine synthesis in the rat brain in vivo - A. Sastre-Coll; S. Esteban; J. A. García-Sevilla (Naunyn-Schmiedeberg's Archives of Pharmacology, 1999)

In situ measurements of skeletal muscle power output using new capacitive strain gauge - P. G. Cooper; G. J. Wilson; D. T. A. Hardman; O. Kawaguchi; Y. -F. Huang; A. Martinez-Coll; R. Carrington; E. Puchert; R. Crameri; C. Horam; S. N. Hunyor (Medical & Biological Engineering & Computing, 1999)

Avocado shoot culture, plantlet development and net CO2 assimilation in an ambient and CO2 enhanced environment - Witjaksono; Bruce A. Schaffer; Angel M. Colls; Richard E. Litz; Pamela A. Moon (In Vitro Cellular & Developmental Biology - Plant, 1999)

A model to study fish DNA immersion vaccination by using the green fluorescent protein - M. Fernandez‐Alonso; F. Alvarez; A. Estepa; R. Blasco; J. M. Coll (Journal of Fish Diseases, 1999)

G disulphide bond native conformation is required to elicit trout neutralizing antibodies against VHSV - M. Fernandez‐Alonso; F. Alvarez; A. Estepa; J. M. Coll (Journal of Fish Diseases, 1999)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Influence of substrate and deployment time on fish assemblages on an artificial reef at Formentera Island (Balearic Islands, western Mediterranean) - J. Coll; J. Moranta; O. Reñones; A. García-Rubies; I. Moreno (Hydrobiologia, 1998)

Sequential G-banding FISH on human sperm chromosomes - P. Colls; C. Templado; O. Martinez-Pasarell; F. Darroudi; A. T. Natarajan (Chromosome Research, 1997)

The 10th Conference of the Entomological Society of Israel - Rachel Galun; I. Ishaaya; Sara Yablonski; Zmira Mendelson; Y. Mansour; Svetlana Kontsedalov; U. Pluschkell; A. R. Horowitz; A. R. Horowitz; Sara Yablonski; Zmira Mendelson; I. Ishaaya; et al. (Phytoparasitica, 1997)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)

The free nucleocapsids of the viral haemorrhagic septicaemia virus contain two antigenically related nucleoproteins - B. Basurco; F. Sanz; M. A. Marcotegui; J. M. Coll (Archives of Virology, 1991)